Women in Local Politics: A Study of Women's Participation in the Politics of Sabaragamuwa Province from 1987-2005 - Hemalatha, R.P.S. (My University, 2007)
This thesis presents a socio-political analysis on women's participation in local politics and identifies the existing constraints which prevent women's participation in politics in Sri Lankan society. It explores the following problem: why is that women's participation in the democratic political process in Sri Lanka has been very low, despite the growth of electoral democracy and the relatively higher conditions for women?. For this study the field survey was carried out in the Sabaragamuwa province. The overall objective of this study is to understand the contexts, conditions and circumstances under which participation of women in local politics in Sri Lanka occur. In this context, special attention is drawn to identify the level of women's participation in the political process and at decision- making levels. In addition to the above aim, reasons for the gender disparity of representation at the local political arena and recognize the means to overcome the existing barriers which limit women's participation in local politics are also examined. For this study, whereas both qualitative and quantitative approaches and two sets of surveys were employed. The survey of perceptions among the general public and women candidates, which consisted of 600 and 110 respondents respectively, selected using the technique of simple random sampling and purposive sampling. Questionnaires and Informal interviews were used to elicit qualitative information. The study reveals that women in ancient society of Sri Lanka have enjoyed the rights of education, holding property, economic, and political participation. Although there are positive evidence to suggest that the pre-colonial society was very often not a gender biased and patriarchal, the strong women and women in royal families and powerful women or the independent women were always not ideal types of women in the pre-modern society Sinhala society. However, in the contemporary Sri Lankan society, women get lesser opportunities in the spheres of economic, political